Taking of Tiger Mountain [videorecording (DVD)] - Zhang, Hanyu, 1964-; Liang, Jiahui; Lin, Gengxin, 1988-; Qu, Bo, 1923-2002 (Well Go USA Entertainment, 2015)
Ka-fai is a ruthless bandit stealing and ruling land from his fortress atop Tiger Mountain. Gengxin captain of the People's Liberation Army launches attacks on the mountain fortress to overthrow the dictator.